PETROGRAPHIC AND OXYGEN-ISOTOPIC STUDY OF REFRACTORY FORSTERITES FROM R-CHONDRITE DAR AL GANI 013 (R3.5-6), UNEQUILIBRATED ORDINARY AND CARBONACEOUS CHONDRITES - Pack A.; Yurimoto H.; Palme H. (My University, 2004)
We have conducted petrographic, chemical and in-situ oxygen isotopic studies of refractory forsterites from unequilibrated ordinary and carbonaceous chondrites as well as an unequilibrated R-chondrite. Refractory forsterites occur in all types of unequilibrated chondrites and all have very similar chemical composition with low FeO and high refractory lithophile element (RLE) contents. Refractory forsterites are typically enriched in 16O relative to ‘normal’ olivine independent of the bulk O-isotope ratios of the parent meteorites. Analyses of refractory forsterites spread along a Δ17O mixing line with Δ17O ranging from +2 to −10‰. Due to similarities in oxygen isotopes and chemical compositions, we conclude that refractory forsterites of various types of chondrites come from a single common reservoir. Implications of this hypothesis for the chemical and O-isotope evolution of silicates in the early solar nebular are discussed.
Keywords: forsterite